Podolsky's Electrodynamics Via First Principles - Jorge Henrique de Oliveira Sales (The Journal of Engineering and Exact Sciences)
A theory of electromagnetism with higher order derivatives, which attained by generalizing the laws of electrostatics, laws that follow from the generalized Coulomb's law and the superposition principle, so that they are consistent with special relativity.